2019
DOI: 10.1371/journal.pbio.3000131
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen diversity drives the evolution of generalist MHC-II alleles in human populations

Abstract: Central players of the adaptive immune system are the groups of proteins encoded in the major histocompatibility complex (MHC), which shape the immune response against pathogens and tolerance to self-peptides. The corresponding genomic region is of particular interest, as it harbors more disease associations than any other region in the human genome, including associations with infectious diseases, autoimmune disorders, cancers, and neuropsychiatric diseases. Certain MHC molecules can bind to a much wider rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 90 publications
1
64
0
1
Order By: Relevance
“…Our findings suggest that, under threat by multiple viruses, antiviral genes such as MxA appear to be under evolutionary pressure to harbor more broadly active alleles even at the expense of more potent, specific antiviral activity. This result is reminiscent of a recent study, which reported that generalist (promiscuous) MHC class II alleles are selected for in human populations in response to high pathogen diversity [22]. Similar breadth-specificity tradeoffs have also been invoked in the case of cytochrome p450 detoxification genes that protect herbivorous insects from plant counterdefenses [23] and in plant disease resistance (R) genes encoded by the Leucine Rich Repeat (LRR) gene family [24].…”
Section: Discussionmentioning
confidence: 60%
“…Our findings suggest that, under threat by multiple viruses, antiviral genes such as MxA appear to be under evolutionary pressure to harbor more broadly active alleles even at the expense of more potent, specific antiviral activity. This result is reminiscent of a recent study, which reported that generalist (promiscuous) MHC class II alleles are selected for in human populations in response to high pathogen diversity [22]. Similar breadth-specificity tradeoffs have also been invoked in the case of cytochrome p450 detoxification genes that protect herbivorous insects from plant counterdefenses [23] and in plant disease resistance (R) genes encoded by the Leucine Rich Repeat (LRR) gene family [24].…”
Section: Discussionmentioning
confidence: 60%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ by extension, in mixed populations with high proportions of Native American ancestry) might result from the frequency increase of some alleles that provide efficient immune protection against highly prevalent extracellular pathogens in specific populations 6,7,15,19,72 .…”
Section: Discussionmentioning
confidence: 99%
“…The class II HLA evolutionary mechanisms proposed by Sanchez-Mazas et al 6 apply particularly to HLA-DQA1 and HLA-DQB1, whereas as noted previously the Lacandon also exhibit relatively low diversity in HLA-DRB1. Certain HLA alleles appear to be promiscuous and are capable of binding an exceptionally large set of epitope peptide segments 15 . Since the HLA class II alleles commonly found in Native Americans (except for HLA-DRB1*16:02), and specifically those reported here for Lacandon Mayans, do not fall within the category of "promiscuous alleles" established by Manczinger et al 15 , we can in principle hypothesize that selection events happening in recent times may have driven this genetic structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A humán leukocita antigén (HLA) molekulákat kódoló gének bioinformatikai vizsgálatával kimutattuk, hogy bizonyos HLA variánsok a többinél sokkal több, eltérő epitópot képesek megkötni (31). Ezek olyan területeken terjedtek el, ahol sok eltérő kórokozó faj található, így az ott élők immunrendszere képessé válik a környezetben található mikrobák hatékony felismerésére és elpusztítására (32).…”
Section: Immuninformatikai Kutatások: úJ Megközelítés Immunmediált Beunclassified